2004
DOI: 10.1177/004051750407400911
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of MVS Yarns in Comparison with Ring Yarns and Open-End Rotor Spun Yarns

Abstract: The structure and properties of Murata vortex spun yarns are investigated and compared with ring and open-end rotor spun yarns. Cotton yarns are spun from the same lot of Australian raw cotton fibers using the Murata vortex, ring, and open-end rotor spinning methods. Yarn structures are observed with an optical microscope equipped with a digital camera. Based on the digitized photographs, fiber arrangements are classified as wild, wrapper-wild, wrapper, belly-band. and core. Yarn diameter, yarn helix angle, wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 3 publications
4
46
0
2
Order By: Relevance
“…From the stand point of hairiness values, VS yarn shows the lowest value, followed by OES, CS and RS yarns, respectively. Soe et al [12] reported that, more than half of the surface area of VS yarn is covered and packed by the layer of wrapper fibers. The uniform arrangement of the wrapper fibers makes the VS yarn the least hairy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the stand point of hairiness values, VS yarn shows the lowest value, followed by OES, CS and RS yarns, respectively. Soe et al [12] reported that, more than half of the surface area of VS yarn is covered and packed by the layer of wrapper fibers. The uniform arrangement of the wrapper fibers makes the VS yarn the least hairy.…”
Section: Resultsmentioning
confidence: 99%
“…The number of independent research works about the vortex spun yarn is very limited, and they particularly deal with the over-viewing of the system, the yarn structure and the role of process parameters in influencing the structural changes of vortex yarns [10][11][12]. The purpose of this paper is to study the properties of knitted fabrics from vortex yarn (VS) in comparison with fabrics knitted from ring spun (RS), open-end rotor spun (OES) and compact yarns (CS), when all other factors, such as yarn count and fabric tightness are held constant.…”
Section: Introductionmentioning
confidence: 99%
“…By the help of the A Nikon SMZ 1500 microscope with a DXM 1200 digital camera, they investigated the side visual assessment of the yarn structures [7]. The fiber arrangements of the RS, OERS and MVS yarns, including the MVS yarn with the tracer fibers were observed carefully.…”
Section: Structure Of Vortex Yarnmentioning
confidence: 99%
“…They adopted the classification by Chasmawala et al [8] and modified it for ring, Open-End and vortex yarns. Description of each classification depending fiber arrangement is explained below [7]:…”
Section: Structure Of Vortex Yarnmentioning
confidence: 99%
“…Therefore, it is necessary to combine the composition of fiber materials with the diversification of yarn structures in order to improve the properties of textile products [1][2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%